New Plants for Florida: Watermelon - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
FAES leased a tract of land near Leesburg, Florida in 1930 for watermelon research. Emphasis in the early years of the program was resistance to Fusarium wilt, and many crosses and selections were made with the objective of developing new, wilt-resistant varieties. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.